1968
DOI: 10.1121/1.1911288
|View full text |Cite
|
Sign up to set email alerts
|

Study of Tinnitus Induced Temporarily by Noise

Abstract: Subjects were exposed in one ear for 5 min to «-oct band noise centered at either 2, 3, 4, or 6 kHz at 110 dB SPL. The resulting aftersensation, called "noise-induced short-duration tinnitus" (NIST) was matched for pitch and loudness in the nonstimulated ear. It was found that the pitch of NIST bears a constant relation to the frequency of the stimulus and that the difference between the equivalent frequency of NIST and the frequency of maximum threshold shift was equivalent to one critical band.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
49
1
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 0 publications
12
49
1
1
Order By: Relevance
“…Chronic tinnitus was induced by unilateral acoustic trauma, i.e., a single exposure to a 4 kHz tone at 80 dB (SPL), which produced a moderate temporary ipsilateral threshold elevation. Acoustic trauma in humans is commonly associated with tonal tinnitus (Loeb and Smith, 1967;Atherley et al, 1968). In the present study, chinchillas exposed to acoustic trauma showed a significant bilateral elevation of putative DCN fusiform cell spontaneous activity.…”
Section: Dcn Activity and Tinnitussupporting
confidence: 52%
See 1 more Smart Citation
“…Chronic tinnitus was induced by unilateral acoustic trauma, i.e., a single exposure to a 4 kHz tone at 80 dB (SPL), which produced a moderate temporary ipsilateral threshold elevation. Acoustic trauma in humans is commonly associated with tonal tinnitus (Loeb and Smith, 1967;Atherley et al, 1968). In the present study, chinchillas exposed to acoustic trauma showed a significant bilateral elevation of putative DCN fusiform cell spontaneous activity.…”
Section: Dcn Activity and Tinnitussupporting
confidence: 52%
“…When acute tinnitus is experimentally induced in human subjects using acoustic trauma, the resulting tinnitus is typically tonal, although its pitch has been reported to be quite variable. When the trauma stimulus was a pure tone, tinnitus frequency tended to be higher than the trauma frequency (Loeb and Smith, 1967), whereas 1/3-octave band noise produced tinnitus that was of lower frequency than the trauma stimulus (Atherley et al, 1968). In the present study, the maximum temporary unilateral threshold elevation, caused by ipsilateral trauma at 4 kHz, appeared between 6 and 8 kHz (Fig.…”
Section: Tinnitus Versus Hearing Losssupporting
confidence: 46%
“…The horizontal dashed line indicates the .01, one-tailed criterion level as that induced by salicylate or other chemicals. However, since it is well established that tinnitus caused by exposing one ear to a loud sound is always lateralized to the exposed ear (Atherley et al, 1968;Davis et al, 1950;Loeb & Smith, 1967), this procedure should work well for tinnitus caused by overstimulating or otherwise damaging one ear.…”
Section: Discussionmentioning
confidence: 99%
“…The three available studies of sound-induced tinnitus in humans suggest that we may make this assumption (Atherley, Hempstock, & Noble, 1968;Davis et al, 1950;Loeb & Smith, 1967). Specifically, each of these studies determined the preexposure absolute thresholds of the subjects, exposed one ear to loud sounds, determined the postexposure absolute thresholds in the exposed ear, and had the subjects match the resulting tinnitus to tones presented to the unexposed ear.…”
mentioning
confidence: 99%
“…Central tinnitus models, on the other hand, are able to account for these tinnitus subtypes. Conversely, central tinnitus models hardly account for acute tinnitus induced immediately after noise trauma [Loeb and Smith, 1967;Atherley et al, 1968] as the noise-induced hyperactivity in the auditory centres takes a few minutes to hours to develop Mulders and Robertson, 2013]. It has been proposed, however, that acute noise-induced tinnitus could be related to the cortical hypersynchrony resulting from the rapid unmasking of thalamocortical connections after noise trauma .…”
Section: Resultsmentioning
confidence: 99%